0657 Evening chronotype moderates the relationship between maternal and offspring's depressive symptoms in a clinical population of adolescents. (25th May 2022) - Sun, Wanqi; Jiang, Yanrui; Wang, Guanghai; Wei, Wenjing; Wu, Hongying; Yuan, Chengmei; Fan, Juan; Li, Shirley; Jiang, Fan
Abstract: Introduction: Although depression has shown a strong familial aggregation tendency, there are some moderators between parental and offspring's depression. Meanwhile, it is known that evening chronotype is a risk factor for depression. Therefore, this study aimed to evaluate the moderating role of chronotype in the relationship between maternal and adolescent depressive symptoms in a clinical sample. Methods: Seventy-five adolescents who visited a sleep or psychiatric clinic with a major complaint of sleep disturbance or emotional problems agreed to participate, 51 adolescents and at least one biological parent who completed questionnaires were included in the current analysis (17 male adolescents, aged 9-17 yrs). Adolescent's chronotype were measured by the reduced Morningness-Eveningness Questionnaire (rMEQ). Depressive symptoms in adolescents and parents were assessed by the Depression Self-Rating Scale for Children (DSRSC) and the Patient Health Questionnaire (PHQ-9), respectively. General linear models were applied to examine the interaction between parental depression and adolescent's chronotype on adolescent's depression, in which age and gender were entered as covariates. Results: Mothers of adolescents with clinical depression (DSRSC>15, n=38) also reported more depressive symptoms (PHQ-9: 4.81±4.37 vs. 2.69±2.46, t=-2.14, p=0.039). But father's depressive symptoms were not related with adolescent's depression. In the current clinical sample, the prevalence of evening chronotype in adolescents was up to 45.1% (n=23). Adolescents with either non-evening or evening chronotype reported comparable level of depressive symptoms (DSRSC: 20.37±6.26 vs. 19.00±8.42, t=0.66, p=0.513). There was a significant interaction between maternal depressive symptoms and chronotype on offspring's depressive symptoms (F=4.05, p=0.044). Specifically, maternal depressive symptoms were associated with offspring's depressive symptoms only in adolescents with evening chronotype. Conclusion: Our study suggested that adolescents with evening chronotype might be at an elevated risk of the transgenerational transmission of depression. Hence, our findings supported the need to consider circadian factors and maternal depression in identifying at-risk adolescents. Support (If Any): This work was supported by the Shanghai Sailing Program awarded to Dr. Wanqi Sun (Shanghai Science and Technology Committee, 19YF1442200).